Banned In Boston: Censorship and Self-Censorship In Boston's Federal Theatre Project. - Vandewalle, Sarah C. (Tufts University. Tisch Library., 2015)
A discussion of Boston's censorship tradition in the early twentieth censorship, as it affected the Federal Theatre Project chapter there in the 1930s. The Federal Theatre Project was a national theatre that was part of Roosevelt's WPA, and in Boston it met censorship obstacles. Consequently, the group began to repress radicalism in its own material in order to avoid external censorship and controversy, by carefully choosing plays, revising scripts, and selectively promoting material. Submitted in partial fulfillment of the grant requirement of the Tufts Summer Scholars Program.